Desfechos perinatais e neonatais de gestações expostas à Covid-19 em uma maternidade de atenção terciária - Damasceno, Sandra Helena Sampaio (2022)
Introduction: Emerging infections caused by a new coronavirus, SARS-CoV-2, emerged in China at the end of 2019, causing a disease called COVID-19 that affected global public health. Brazilian statistics on the severity of the disease affecting its obstetric population and the limited national production of studies involved in the context of newborn care during the pandemic support investigations that can add knowledge to positively influence the care and health of newborns. Objectives: 1) to present perinatal and neonatal outcomes of pregnancies exposed to SARS-CoV-2 infection; 2) characterize the clinical profile of its population; 3) describe and analyze the factors associated with negative outcomes; and 4) Relate perinatal and neonatal outcomes of fetuses/newborns of women with the severe form of the disease and women with mild symptoms. Method: This is a cross-sectional, descriptive, analytical study, with a documentary approach, through the analysis of the medical records of mothers diagnosed with COVID-19, confirmed through the RT-PCR exam, and their newborns, who were hospitalized at the Maternity School Assis Chateaubriand (MEAC), in Fortaleza, Ceará, from April 2020 to April 2021. The study population corresponded to the medical records of these women and their conceptuses. A time frame was chosen in the period of twelve months and the sampling was of the non-probabilistic type. The collected data were analyzed using the statistical software IBM – SPSS Statistics – v.22 and JAMOVI – version 2.0. For quantitative variables, measures of central tendency, measures of dispersion, identification of minimum and maximum values were calculated. While for the qualitative variables, their absolute and relative frequencies were calculated and presented in univariate tables. For the inferential analysis, non-parametric tests were used. For continuous variables, for independent samples, the median, unpaired Mann–Whitney and/or Kruskall-Wallis tests were applied. Inferences for qualitative variables were analyzed using Pearson's chi-square test or Fisher's exact test. The significance level (α) adopted was 5% and the confidence interval established was 95%. The dissertation is presented in the form of three articles. Results: The first article “Perinatal and Neonatal Outcomes of Pregnancies Exposed to COVID-19 in a Tertiary Care Maternity” describes the profile of the investigated population and presents its results. The average age of pregnant women was 26 years old, being the majority from Fortaleza (61.5%), with high school education (53.9%), stable union (50.8%) and having as occupation of the home/student (61.5%). Regarding the current obstetric history, the average number of prenatal consultations was six (SD=3), 60% were multiparous, 98.5% were in the 3rd gestational trimester, 41.5% were less than 37 weeks pregnant gestational age on the date of delivery, with cesarean section being the chosen route of delivery (87.7%). Regarding perinatal and neonatal outcomes, the predominance was of live births (95.5%), with a prevalence of 3.0% of intrauterine fetal death and 1.5% of early neonatal death. Related to gestational age, 20% of neonates were very preterm, 13.9% were late preterm, 6.1% were moderate preterm and only one was extremely preterm (1.5%). As for weight, 20.6% were Low Weight Newborns and 11.1% were Very Low Weight Newborns. The 1st and 5th minute Apgar means were 8 and 9 respectively, with 20.5% of neonates presenting a 1st minute score compatible with moderate or severe anoxia (< 7). 23.8% of the babies needed resuscitation in the delivery room and admission to the Neonatal Intensive Care Unit occurred in 33.3% of the cases investigated. The mean neonatal hospital stay was 17 days. Only two neonates had a detectable RT-PCR test for COVID-19. The second article “Repercussions of Severe Maternal Acute Respiratory Syndrome by COVID-19 on Perinatal and Neonatal Outcomes” relates the perinatal and neonatal outcomes of newborns of women with the severe form of the disease and women with mild symptoms. SARS affected 36.9%. The cesarean delivery method represented 87.7% of all cases analyzed, having been the most common form of delivery among women with and without SARS (95% CI: 0.5 – 20.7; p-value = 0.126). There was a statistically significant relationship between maternal SARS and prematurity (95% CI: 2.1 – 9.8; p-value: < 0.001), as well as an association between maternal SARS and low birth weight (95% CI: 1.6 - 5.8; p-value: < 0.001). When checking the Apgar score in the 1st minute, it was possible to observe a lower performance (<7) in children born to mothers who had SARS (95% CI: 2.1 – 6.2; p-value: < 0.001). There was an influence of maternal severity on neonatal outcomes of resuscitation in the delivery room (95% CI: 3.6 – 64.4; p-value: < 0.001), admission to the Neonatal Intensive Care Unit (NICU) (95% CI: 2.6 – 27, 9; p-value: < 0.001), in neonatal respiratory distress syndrome (95% CI: 1.6 – 7.9; p-value: < 0.001), duration of ventilatory support use (p-value: < 0.001 ) and length of hospital stay (p-value: < 0.001). The third article “Good Birth Care Practices in the Context of the COVID-19 Pandemic in a Tertiary Care Maternity” presents the results regarding the management of good practices in the investigated population, in which the timely clamping of the umbilical cord was observed. in 69.8% of births. Skin-to-skin contact in the delivery room was not performed in 84.1% of births, as well as breastfeeding in the 1st hour of life in 88.9% of them. 49.2% of the neonates stayed in rooming with their mothers. At hospital discharge, 44.2% of the newborns had exclusive breastfeeding as a form of diet and 42.6% of them were being formula fed. 16.9% of the babies were discharged from the hospital without the mother. Maternal severity characterized by SARS influenced the outcomes of rooming-in (95% CI: 0.1 – 0.4; p-value: < 0.001) and formula diet at hospital discharge (95% CI: 49.7 – 86.3; p-value: < 0.001). Conclusion: Maternal infection with SARS-CoV-2 can lead to unfavorable outcomes such as cesarean delivery, prematurity and low birth weight. The study had limitations regarding the possibility of vertical transmission. The maternal severity condition characterized by the presence of SARS by COVID-19 did not influence outcomes such as mode of delivery, fetal vitality and gestational age/weight. On the contrary, it seemed to have repercussions on unfavorable perinatal and neonatal outcomes such as prematurity, low birth weight, neonatal asphyxia, resuscitation in the delivery room, NICU stay, length of hospital stays, RDS and use of ventilatory support. Results that, in the face of maternal severity, point to the need for care teams prepared to provide agile and effective care that guarantees the survival of newborns and their mothers. Maternal COVID-19 seems to have hampered the implementation of good birth care practices and, consequently, may have resulted in compromising the initial establishment of the mother-baby bond in the investigated population. Current evidence points to the continuity of usual care in institutions that provide assistance to this population.